Granting Partial Confidence to The Ministry in Constitution of The Republic of Iraq 2005 - عبيد عدنان عاجل; طالب مصدق عادل (Journal of Legal Sciences, 2021)
The Topics of Granting Confidence to the Ministry is a Renewed Issue in the Constitutional and Practical Reality. This is important if we know that although the Constitution of the Republic of Iraq does not address this issue, the Federal Supreme Court of Iraq has established new provisions regarding the granting of partial confidence to the Government despite the clarity and openness of the text of the article (76) of the Constitution of the Republic of Iraq for the year 2005, and therefore this study attempts to answer the following questions: Does the Federal Supreme Court have the amendment of the constitutional text? Is it possible to consider the decision of the Federal Court a customary constitutional custom of deletion if we know the frequency of Iraqi governments formed from the first electoral cycle in 2006 and ending the fourth electoral cycle in 2018 to follow these principles? Is the conduct of the comparative constitutions regarding the granting of confidence to the ministry is consistent with the position of the constitutional legislator or not ?